VALORIZATION OF PHOSPHATE WASTES FROM THE DJEBEL ONK MINE FOR BETTER ENVIRONMENTAL MANAGEMENT - ZEGHINA, Sara Imane; KHELIFI, Walid; BOUSLAMA, Amina; BENSELHOUB, Aissa (GeoScience Engineering, 2024)
Algerian phosphates are the most exploited mineral resource and are considered an important source of foreign currency and a vital element in the mining sector. However, phosphate waste must be valorized for the product to be marketable. Phosphate waste, treated through washing and calcination, meets industrial requirements and international standards, with a P2O5 content of 31 %. Various tests of calcination and washing of phosphate waste are carried out to thermally dissociate the carbonates of the exogenous and endogenous gangue from the ore within a temperature range typically between 700 and 1000 °C. To reduce the proportions of CaO and MgO compared to P2O5, the second important step involves hydrating the oxides of Ca and Mg to subsequently remove them. Algerian phosphates are the most exploited mineral resource and are considered an important source of foreign currency and a vital element in the mining sector. However, phosphate waste must be valorized for the product to be marketable. Phosphate waste, treated through washing and calcination, meets industrial requirements and international standards, with a P2O5 content of 31 %. Various tests of calcination and washing of phosphate waste are carried out to thermally dissociate the carbonates of the exogenous and endogenous gangue from the ore within a temperature range typically between 700 and 1000 °C. To reduce the proportions of CaO and MgO compared to P2O5, the second important step involves hydrating the oxides of Ca and Mg to subsequently remove them. According to this study, it can be concluded that the calcination and washing method can be applied to phosphate waste, as it has increased P2O5 content. This technique is simple and cost-effective and does not require heavy investments in industrial equipment.